Melampaui Hegemoni Sekuler: Reinterpretasi Kewirausahaan Guru (Teacherpreneurship) dalam Kerangka Habluminannas dan Habluminallah - Farida Nurul Khasanah; Rifka Nur Rahmawati; Muhammad Futuhal Arifin; Nadhira Fitri Fidiyanti; Edy Kurniati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Discussions on teacher entrepreneurship (teacherpreneurship) are increasingly prominent in line with the growing demands of modern education, which emphasizes creativity, independence, and innovative abilities of educators. However, this discourse is often framed by a secular perspective that emphasizes productivity and material gain as the primary orientation. As a result, spiritual values and divine ethics are often diminished. Based on this situation, this paper attempts to reinterpret the concept of teacherpreneurship through an Islamic approach, referring to the principles of hablumminallah and hablumminannas as moral and philosophical foundations. Based on a literature review and theoretical studies on Islamic education and entrepreneurship, the concept of Islamic Teacherpreneurship is proposed as a form of entrepreneurship that emphasizes not only economic aspects but also strengthens awareness of worship and social benefits. The hablumminallah perspective directs the role of teachers so that their efforts are worshipful and full of integrity, while hablumminannas demands a real contribution to the environment and society. Thus, this model can be an alternative to secular patterns that tend to be materialistic and open new opportunities for strengthening teachers' entrepreneurial character in a more comprehensive and meaningful way. This study also provides recommendations for the concept of Islamic Teacherpreneurship to be further developed through empirical studies in educational institutions.